Mixed Messages: The Early Modern Reception of Eusebius as a Church Historian. - Grafton, Anthony (International Journal of the Classical Tradition, 2020)
The article focuses on early modern reception of Eusebius as a Church historian. It mentions that Eusebius is not just the author of the Ecclesiastical History, whose extensive quotation of sources inspired the format of early modern histories like those of Baronio and Flacius. It also mentions about his contribution to scholarship on the nature and development of early modern historiography.